Tribulus terrestris Linn.: A Novel Natural Preservative for Improved Lipid Stability and Storage Quality of Meat Products - Noor, Sabahu; Bhat, Z. F.; Kumar , Sunil; Kalem , Insha Kousar (Journal of Meat Science, 2018)
A study was conducted to evaluate the potential of Tribulus terrestris as a novel natural preservative in meat products. Chevon sausages were used as a model system and incorporated with different levels of T. terrestris viz. T1 (0.25%), T2 (0.50%) and T3 (0.75%) and were vacuum packaged and assessed for various lipid stability and storage quality parameters under refrigerated (4±1OC) conditions. Sig nificantly (p<0.05) lower TBARS (mg malonaldehyde/kg) values were observed for the products containing T. terrestris. A significant (P<0.05) effect was also observed on the microbial stability as T. terrestris containing products showed lower total plate count (log cfu/g), psychrophilic count (log cfu/g), yeast and mould count (log cfu/g), anaerobic count (log cfu/g) and FFA (% oleic acid) values.Signifi cantly (p<0.05) higher scores were observed for various sensory parameters of the products containing T. terrestris (0.25%). T. terrestris successfully improved the lipid stability and storage quality of the model meat product under vacuum packaging conditions and might be commercially utilized as a novel natural preservative for muscle foods.